L’économie de la responsabilité sociétale d’entreprise (RSE) :éléments de méthode institutionnaliste - Jean-Pierre Chanteau (Revue de la Régulation)
The corporate social responsibility (CSR) integrates both political and moral dimensions which exceed the social performance of the firm –that is the usual topic of the economics of the CSR– but impacts it so this dimensions must be addressed by the economic analysis. This paper provides some methodological tools to do so. The first part presents the analysis framework of symbolic quality signals that aim at characterizing the criteria of a quality, proving compliance and making it competitive. Besides there is a particular difficulty while this quality –typical of credential goods– refers to some properties of productive organizations or products that cannot be checked by using them. The second part shows that: a) the current CSR-quality signals do not fit the required institutional conditions of identity, compliance and profitability so they cannot set the CSR prosocial behavior as a widespread though non legal norm; b) a managerial-type CSR and a political-type CSR are trying for two very different ways of operating business and governing firms.